SYSTEMATIC REVIEW HUBUNGAN ANTARA KEPATUHAN PENGOBATAN ORAL ANTIDIABETES DAN GAGAL GINJAL PENDERITA DIABETES MELLITUS - Firdianita Nuria Orbanida; Moh. Arie Wurjanto; Ari Udijono; Henry Setyawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Knowledge, Belief, Attitude, Drug Amount, Family Support, Physical Activity, Carbohydrate Intake and Pharmacological Therapy related to DM control with medication adherence and kidney failure in DM patients. This review aims to identify articles regarding adherence to oral antidiabetic drugs and kidney failure in DM patients. Search articles in several databases using keywords in the 2011-2020 period and gray literature. Search libraries using online databases such as MEDLINE, Proquest, Garuda Journal and Google Scholar. Review synthesis using STROBE. Sixteen research articles for review. Taking medication and kidney failure in DM patients are related to the compliance of DM patients. Non-compliance with DM patients through DM control behavior (physical activity, carbohydrate intake, control of blood glucose levels) and awareness for treatment is still low. Motivation, family support and a good relationship between doctors and patients can have an influence on the obedient behavior of DM patients.